The structural adjustment programme and deforestation in Ghana - Benhin, J.K.; Barbier, Bruno (2000)
Ghana’s Structural Adjustment Programme (SAP) was begun in 1983 to reverse economic decline through resource mobilisation, public sector and institutional reforms, and market liberalisation in order to promote growth. Recognising the need for agriculture to lead any sustained overall economic growth, both short and medium term policies and strategies have been implemented. The objective of the SAP was to eliminate supply-demand imbalances in the agricultural sector by providing incentives to expand production. The policies were grouped as follows: improving agricultural productivity; reducing risk and uncertainty factors associated with production and post-harvest activities; enhancing production incentives; providing the required support infrastructure. The agricultural sector still faces many constraints in production and marketing. Increases in output during the SAP period may be due more to land expansion than to productivity outputs. This has negative implications for forests and biodiversity in Ghana. Both supply and demand-side policies have been used to address deforestation. On the supply side, measures have been taken to control or regulate the supply of timber to concessionaires, and a national tree-planting programme was launched in 1984. On the demand side, the provision of credit facilities, low corporate taxes, exchange rates and foreign exchange retention help improve efficiency in processing and, with an export ban on certain species, help reduce the overuse of tree species. Attention is now being turned to forest fees.